Find peace in a poem poetry about mindfulness - Coe, Mandy (Little Tiger, 2024)
This beautifully illustrated collection features powerful poems written by a wide range of contemporary voices. They share their unique perspectives on the topic of mindfulness, from listening for silence and living in the moment to the colour of our dreams and what the trees can teach us
Cover title
This book includes poetry written in British and American English
Keywords: Achtsamkeit; Englisch; Kinderlyrik; Amerikanisches Englisch; Mindfulness (Psychology) / Juvenile poetry; Children's poetry, English; Bilderbuch; Anthologie